Chaos based Image Watermarking using IWT and SVD - Kala, A Kala; Thaiyalnayaki, K (International Journal of Computer Sciences and Engineering, 2015)
Copyright protection and rightful ownership is needed in the fast growing Internet environment. The watermarking offers a convenient way to hide specific information via an imaging system. In this paper, we proposed a IWT and SVD-based image watermarking scheme by embedding the watermark into the host image. The chaos encryption is applied to the watermark image before embedding into host image to provide robustness. The proposed watermarking algorithm is tested for different attacks. It shows very good robustness and also good quality of watermark is extracted by performing other common image processing operations like brightening, sharpening, contrast enhancement etc. The experimental results demonstrate that the proposed method overcomes the various attacks.